Nasometry Normative Data for 4- to 6-Years-Old Persian Normal Boys in Isfahan City, Iran - Saba Sadeghi; Parisa Rezaei; Zahra Heidari; Fatemeh Derakhshandeh (Vesnu Publications, 2016)
Introduction: Every year, a group of children with velopharyngeal insufficiency (VPI) become candidate for secondary surgery in order to improve their resonance disorder, but the perceptual assessments that are based on clinician's perceptual and quantitative judgments are not responsible for making decisions for secondary surgery. So, the perceptual assessment should be complemented by using aerodynamic and acoustical techniques. Aerodynamic and acoustical techniques are important, because they have potential to provide quantitative results. Nasometer measures the oral and nasal acoustical energy during the speech that is expressed as nasalance score and is a quantitative assessment. The aim of this study was to obtain the normative nasalance scores for 4- to 6-years-old boys speaking Persian language. Materials and Methods: This cross-sectional study was done in 2015 on 4- to 6-years-old Persian children in Isfahan City, Iran. All consented participants were initially screened to identify any overt difficulties relating to hearing, voice quality, resonance or speech and language skills. Mean nasalance scores were obtained from 43 normal speaking boys aged 4 to 6 years during the repetition of Persian version of Simplified Nasometric Assessment Procedures (SNAP) test. The Nasometer (model 6450) was used to obtain nasalance scores. Results: The mean obtained nasalance scores for SNAP test for oral and nasal sentences were 11.57 ± 3.16 and 48.51 ± 7.03, respectively. Conclusion: The present study provides normative nasalance scores for Persian-speaking boys that can be used as a reference in the clinical process including making decision for needing secondary surgery. As the gender and age are the factors that can affect the nasalance score, obtaining nasometer norm in other age groups and sex seems to be necessary.